Role of Erythropoietin in Adherence to Antiviral Treatment in Hepatitis C - Rizwan Ahmed, S.Sabahat Mansur,Faridullah Shah, (Journal of Rawalpindi Medical College, 2013)
Background: To evaluate the role of low dose erythropoietin in the management of drug induced anemia and thus in adherence and continuation of antiviral treatment. Methods: In this descriptive study 370 patients with chronic hepatitis C were included . All patients were given conventional Interferon Alpha-2b plus Ribavirin for 24 weeks. Haemoglobin estimation was done on day 0 and at 2 weekly interval for first month and then monthly for 5 months. Erythropoietin was given to patients with Hb level of 7 gm/dl and less. The study end points were to assess the Interferon maintenance and change in Hb. Results: Out of the 370 patients treated with Interferon Alpha-2b plus Ribavirin, (n=31 patients) 8% were treated with erythropoietin. During erythropoietin treatment the Hb initial mean was 7 gm/dl and improvement of 2gm/dl or more than 2 gm/dl was the end point. In 3 patients, Hb dropped further inspite of erythropoietin treatment, while in 26 patients, Hb improved with erythropoietin treatment. The optimal dose of Ribavirin was maintained in 29 patients throughout the treatment. In 2 patients, Ribavirin dose was decreased due to anaemia not responding to erythropoietin. Conclusion: Even low doses of erythropoietin are effective in improving or maintaining haemoglobin levels in patients with treatment induced anaemia . Reduction of severity of treatment-induced anaemia with erythropoietin has been shown to encourage adherence and to enable patients to remain on higher doses of antiviral treatment